PEMANFAATAN INFORMASI PADA APLIKASI TIKTOK SHOP DALAM JUAL BELI ONLINE OLEH MAHASISWA DERPARTEMEN ILMU INFORMASI DAN PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Yurizal, Sherly; Primadesi, Yona (Scinary, 2023)
This research aims to describe the use of information on the TikTok Shop application as a means of online buying and selling among students of the Information and Library Science Department, Padang State University. This type of research is quantitative research using descriptive methods. The population of this study was 655 students with a sample of 87 respondents. Sampling uses a purposive sampling technique, namely sampling based on certain characteristics. The results of this research show that the use of product information got an average score of 3.07 in the good category, the use of price information got an average score of 2.99 in the good category, the use of transaction information got an average score of 3.18 in the good category and User experience obtained an average score of 3.03 in the good category. Thus, the use of information on the TikTok Shop application in online buying and selling by students of the Department of Information Science and Libraries at Padang State University is said to be good.